Optic variables used to judge future ball arrival position in expert and novice soccer players - Craig, C. M.; Goulon, C.; Berton, E.; Rao, G.; Fernandez, L.; Bootsma, R. J. (Attention, Perception, & Psychophysics, 2009)
Although many studies have looked at the perceptual—cognitive strategies used to make anticipatory judgments in sport, few have examined the informational invariants that our visual system may be attuned to. Using immersive interactive virtual reality to simulate the aerodynamics of the trajectory of a ball with and without sidespin, the present study examined the ability of expert and novice soccer players to make judgments about the ball`s future arrival position. An analysis of their judgment responses showed how participants were strongly influenced by the ball`s trajectory. The changes in trajectory caused by sidespin led to erroneous predictions about the ball`s future arrival position. An analysis of potential informational variables that could explain these results points to the use of a first-order compound variable combining optical expansion and optical displacement.